Psychosis and Schizophrenia - Furtuna, Alexandra-Gabriela (New Trends in Psychology, 2022)
Psychosis usually occurs due to a combination of a person's genetics and life experiences. For others, psychosis may be a feature of a mental health condition, such as; schizophrenia, schizoaffective disorder, bipolar disorder. Substance-induced psychosis treatment involves both immediate treatments, including hospitalization, and long-term care, often in a residential setting and using medications and behavioral therapies. Not everyone who suffers from psychosis has the same symptoms.